Social quality theory : a new perspective on social development - Lin, Ka; Herrmann, Peter, 1955- (Berghahn Books, 2015)
Social quality thinking emerged from a critique of one-sided policies by breaking through the limitations previously set by purely economistic paradigms. By tracing its expansion and presenting different aspects of social quality theory, this volume provides an overview of a more nuanced approach, which assesses societal progress and introduces proposals that are relevant for policy making. Crucially, important components emerge with research by scholars from Asia, particularly China, eastern Europe, and other regions beyond western Europe, the theory's place of origin. As this volume shows, this rich diversity of approaches and their cross-national comparisons reveal the increasingly important role of social quality theory for informing political debates on development and sustainability.